Performing Methods of Undress towards a Re-Imagined African Masculine Identity - Mabitsela, Lesiba (Michaelis School of Fine Art, 2019)
In a continent built on competing patriarchal cultures and traditions, the Eurocentric perspective is dominant. The suit/blazer has become a symbol of morality, power, and class that has centred its position via the violent legacy of colonialism and slavery or as Edward Said defines these legacies, via notions of “cultural imperialism”. The purpose of this paper is to inquire whether an aesthetic change from this ideological legacy would ultimately lead to a change in African masculine embodiments. The research identifies and applies multiple references from different applications of embodied resistance: sartorial displays, fashion design, drapery and theories around the gendered body and its relation to clothing for such a purpose – performed hereas „methods of undress‟.